Virological outcome among HIV infected patients transferred from pediatric care to adult units in Madrid, Spain (1997-2017) - Cervero, Miguel; Beltrán¿Pavez, Carolina; Gutiérrez¿López, Miguel; Rubio¿Garrido, Marina; Valadés¿Alcaraz, Ana; Prieto, Luis; Ramos, José Tomás; Jiménez De Ory, Santiago; Navarro, Marisa; Díez¿Romero, Cristina; Pulido, Federico; Valencia, Eulalia; et al. (Springer Nature, 2020)
The aim of this transversal study was to describe the virological and immunological features of HIV-infected youths transferred from pediatric to adult care units since 1997 vs. the non-transferred patients from the Madrid Cohort of HIV-infected children and adolescents in Spain.We included 106 non-transferred and 184 transferred patients under clinical follow-up in 17 public hospitals in Madrid by the end of December 2017.Virological and immunological outcomes were compared in transferred vs. non-transferred patients.ART drug resistance mutations and HIV-variants were analyzed in all subjects with available resistance pol genotypes and/or genotypic resistance profiles.Among the study cohort, 133 (72.3%) of 184 transferred and 75 (70.7%) of 106 non-transferred patients had available resistance genotypes. Most (88.9%) of transferred hadART experience at sampling.A third (33.3%) had had a triple-class experience.Acquired drug resistance (ADR) prevalence was significantly higher in pretreated transferred than non-transferred patients (71.8% vs. 44%; p= 0.0009), mainly to NRTI (72.8% vs. 31.1%; p< 0.0001) and PI (29.1% vs. 12%; p= 0.0262). HIV-1 non-B variants were less frequent in transferred vs. non-transferred (6.9% vs. 32%; p< 0.0001). In conclusion, the frequent resistant genotypes found in transferred youths justifies the reinforcement of HIV resistance monitoring after the transition to avoid future therapeutic failures.